The impact of the COVID-19 pandemic on respiratory failure caused by respiratory viruses in children and adolescents - Gama, Thiago Belem; Ferraro, Alexandre A.; Vieira, Sandra E. (Frontiers in Pediatrics, 2024)
Background: In addition to the direct impact of the coronavirus disease 2019 (COVID-19) pandemic on child/adolescent health, changes in infections caused by other viruses have been observed. Respiratory syncytial virus (RSV) and influenza are important agents of acute respiratory failure (ARF) in these age groups. This study presents an analysis of the influence of the pandemic on the seasonal and clinical patterns of ARF caused by RSV and influenza.Methods: A retrospective ecological study was performed. The data of individuals younger than 20 years who were hospitalized with ARF and who were diagnosed with RSV, influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) between 2019 and 2022 were analysed. The data were collected from the governmental system.Results: Among 367,136 individuals, the incidence of ARF increased annually. During the pandemic, the number of infected schoolchildren, adolescents, and nonwhite people; intensive care admissions; and mortality rates increased. Older age, SARS-CoV-2 infection, and residence in North Brazil/Northeast Brazil were associated with lower odds of intensive care unit admission but greater odds of death. Comorbidities were important risk factors for severe disease. There was a drastic reduction in the number of RSV and influenza infections, with a resurgence in 2021. After the resurgence in 2021, the number of influenza-related deaths remained above the 2019 level, which did not occur in 2022. After 2021, RSV infection was associated with greater odds of intensive care admission but not death.During the pandemic, older children, adolescents, and individuals with comorbidities were more vulnerable to ARF. There was a reduction in the prevalence and severity of RSV and influenza infections. After this reduction, a resurgence with an out-of-season pattern, but without higher odds of death than in the prepandemic year, was observed for both in 2022.